Role of Emergency Laparoscopic Colectomy for Colorectal Cancer: A Population-based Study in England - Vallance, Abigail E; Keller, Deborah S; Hill, James; Braun, Michael; Kuryba, Angela; van der Meulen, Jan; Walker, Kate; Chand, Manish (Annals of surgery, 2019)
To evaluate factors associated with the use of laparoscopic surgery and the associated postoperative outcomes for urgent or emergency resection of colorectal cancer in the English National Health Service. Laparoscopy is increasingly used for elective colorectal cancer surgery, but uptake has been limited in the emergency setting. Patients recorded in the National Bowel Cancer Audit who underwent urgent or emergency colorectal cancer resection between April 2010 and March 2016 were included. A multivariable multilevel logistic regression model was used to estimate odds ratios (ORs) of undergoing laparoscopic resection and postoperative outcome according to approach. There were 15,516 patients included. Laparoscopy use doubled from 15.1% in 2010 to 30.2% in 2016. Laparoscopy was less common in patients with poorer physical status [American Society of Anaesthesiologists (ASA) 4/5 vs 1, OR 0.29 (95% confidence interval, 95% CI 0.23-0.37), P < 0.001] and more advanced T-stage [T4 vs T0-T2, OR 0.28 (0.23-0.34), P < 0.001] and M-stage [M1 vs M0, OR 0.85 (0.75-0.96), P < 0.001]. Age, socioeconomic deprivation, nodal stage, hospital volume, and a dedicated colorectal emergency service were not associated with laparoscopy. Laparoscopic patients had a shorter length of stay [median 8 days (interquartile range (IQR) 5 to 15) vs 12 (IQR 8 to 21), adjusted mean difference -3.67 (-4.60 to 2.74), P < 0.001], and lower 90-day mortality [8.1% vs 13.0%; adjusted OR 0.78 (0.66-0.91), P = 0.004] than patients undergoing open resection. There was no significant difference in rates of readmission or reoperation by approach. The use of laparoscopic approach in the emergency resection of colorectal cancer is linked to a shorter length of hospital stay and reduced postoperative mortality.